Study of Flavoured Dahi Incorporated with Banana Extract - Islam, MS; Mazed, MA; Rahman, S; Akter, MS (Journal of Environmental Science and Natural Resources, 2015)
In Bangladesh, dahi is considered as a yummy nourishing and admired milk product. Dahi is available in the market but it exists in diversified quality in respect of locality. The producers every so often add some ingredients that may reduce or raise the excellence of dahi. This study was intended to evaluate the supremacy and to measure the feasibility of incorporation of banana extract in the manufacture of dahi. Dahi was prepared through boiling of milk, homozinization followed by incorporation of banana juice at different levels and subsequent addition of starter culture. Physical analysis was conducted through organoleptic tests and chemical analysis was done through proximate analysis. The experiment was conducted with 4 treatments (0%, 2%, 4% and 6% banana juice) having 3 replications for each treatment. The differences for body and consistency among various treatments were statistically insignificant in Khulna and Bagerhat coastal regions. Dahi with 2% banana extract was superior in respect of smell and taste in Khulna region. No significant different scores were found for colour and texture among various treatments in Bagerhat region but that of Khulna were highly significant (P<0.01). The differences for colour and texture scores among various treatments were statistically significant in Khulna region (P<0.05) while, that of Bagerhat region were insignificant. Incorporation of banana juice, therefore, improves the organoleptic qualities of dahi. Differences in acidity percentage among the treatments were insignificance in Khulna region but that of the Bagerhat region were statistically significance (p< 0.01). The differences in average fat percentage of plain, 2%, 4% and 6% banana juice made dahi was statistically highly significant (p< 0.01) in Khulna region and significant (P<0.05) in Bagerhat region. The average total solid (TS) , moisture, ash content for plain, 2%, 4% and 6% banana juice made dahi in both regions were insignificant. Incorporation of banana juice might increase organoleptic qualities. Manufacture of maximum volume of dahi from minimum volume of milk incorporating banana extract might definitely profitablize and popularize the milk product business. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22057 J. Environ. Sci. & Natural Resources, 6(1): 153-158 2013